2013
DOI: 10.17231/comsoc.23(2013).1626
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotyping, Sex and Violence in Portuguese and Spanish Advertisement

Abstract: This study analyses the gender stereotypes, sex and violence in advertisements in all media except radio, from Portugal and Spain. We have conducted this study after ascertaining that gender stereotypes, as well as sexual and violent scenes, are embedded in advertisement as a formula to increase the possibility of remembering them. This advertisement analysis explores gender stereotyping, sex and violence, both for the Portuguese and Spanish advertisement market. We used a sample of 245 messages from Portugues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Indeed, gender differences were observed in Studies 1 and 3 where men endorsed more DVMs than women, but no gender difference emerged from Studies 5 and 6. Traditional gender role stereotypes are still very strong in Portugal (e.g., see Costa Pereira, Verissimo, Castillo Diaz, & Correia, 2013), although gender equality is widely promoted (Santos & Pereira, 2013). The adherence to conservative and gender-oppressive ideologies by Portuguese female participants could explain such a gender-null effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gender differences were observed in Studies 1 and 3 where men endorsed more DVMs than women, but no gender difference emerged from Studies 5 and 6. Traditional gender role stereotypes are still very strong in Portugal (e.g., see Costa Pereira, Verissimo, Castillo Diaz, & Correia, 2013), although gender equality is widely promoted (Santos & Pereira, 2013). The adherence to conservative and gender-oppressive ideologies by Portuguese female participants could explain such a gender-null effect.…”
Section: Discussionmentioning
confidence: 99%
“…As evidências sugerem que, embora a estereotipização de género nas campanhas publicitárias tenha vindo a diminuir em alguns casos, ela continua fortemente presente nas mensagens das marcas (Wolin, 2003;Milner & Higgs, 2004;Lindner, 2004;Robinson & Hunter, 2008;Gentry & Harrison, 2010;Furnham & Paltzer, 2010;Eisend, 2010Eisend, , 2019Grau & Zotos, 2016;Matthes, Prieler & Adam, 2016;Veríssimo & Pereira, 2006;Pereira, Veríssimo, Diaz & Correia, 2013;Jorge, Cerqueira & Magalhães, 2014;Pio, 2019).…”
Section: Publicidade E Representações De Génerounclassified
“…This strategy has immediate and delayed effects on the effectiveness of the advertising (Eisend and Langner, 2010). Also, stereotypes in advertising are reinforced by the use of celebrity voices and opinion leaders that prescribe, validate, and approve the products and brands (Costa Pereira et al, 2013). Eisend and Langner (2010), state that not all the effects of advertising are immediate and that the subject could have been reinforced by a previous advertising campaign in order to purchase the product.…”
Section: Advertising and Its Effect On Pricementioning
confidence: 99%
“…Costa Pereira, Verissimo, Castillo Diaz, and Correia (2013) found that, at least in Portugal and Spain, gender stereotypes are closely connected with products and their use. Typically, women's products tend to be either body products or those associated with household tasks, food and consumerism, while products associated with men are connected to socio-economical projection (cars, work, financial investment and sports).…”
mentioning
confidence: 99%